Kierkegaard, Eve and metaphors of birth - Assiter, Alison (Rowman & Littlefield International, 2015)
Contingent and chaotic reality -- A challenge to chaos -- Kant, freedom, and evil -- Kierkegaard and Schelling on process -- The concept of anxiety and Kant -- Kierkegaard on women -- Metaphors of birth in Kierkegaard -- More on birthing -- Nature as a body that can birth -- The age of revolution and the present age